2010
DOI: 10.1002/jcla.20374
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)‐1β, IL‐1 receptor antagonist, IL‐6, IL‐8, IL‐10, and tumor necrosis factor α gene polymorphisms in patients with febrile seizures

Abstract: Inflammation and genetics may play a role in the pathogenesis of febrile seizures (FSs). We aimed to test whether interleukin-1beta (IL-1beta), IL-1 receptor antagonist (IL-1 Ra), IL-6 promoter, IL-8, IL-10, or tumor necrosis factor (TNF) gene polymorphisms could be used as markers of susceptibility to FSs. An association study was performed among a cohort of 104 patients with FSs and 143 normal control subjects. There was no significant difference between patients and controls in the distribution of allele fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 25 publications
0
41
1
Order By: Relevance
“…Emsley et al found no significant association of TNF-α SNPs, but significant result was for missense SNP rs208294 in P2X7R (purinergic receptor P2X7) [41]. Also, Chou et al demonstrated that IL-1 receptor antagonist allele 1 homozygote was more frequent in patients with FS than in healthy controls, but no significant difference was evident in the distribution of allele frequencies of the IL-1B promoter, IL-1B exon 5, IL-6 promoter, IL-8, IL-10, or the TNF-α gene polymorphism [42].…”
Section: Discussionmentioning
confidence: 99%
“…Emsley et al found no significant association of TNF-α SNPs, but significant result was for missense SNP rs208294 in P2X7R (purinergic receptor P2X7) [41]. Also, Chou et al demonstrated that IL-1 receptor antagonist allele 1 homozygote was more frequent in patients with FS than in healthy controls, but no significant difference was evident in the distribution of allele frequencies of the IL-1B promoter, IL-1B exon 5, IL-6 promoter, IL-8, IL-10, or the TNF-α gene polymorphism [42].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the GG genotype was observed at a higher frequency in patients with a family history of seizures, indicating that it could be a risk factor for epilepsy. Reasons for these differences may include geography, ethnicity, and genomic heterogeneity (Tilgen et al, 2002;Chou et al, 2010;Wu et al, 2012). In this study, the GG genotype was the most frequently observed genotype in patients with head trauma and difficult birth, and the G allele frequency was the most common allele.…”
Section: Discussionmentioning
confidence: 60%
“…The results of Kanemoto et al (2003) agree with our results in many aspects. In contrast, no association between epilepsy and IL-1β polymorphisms was noted by Tiwari et al (2012) in India, Chou et al (2010) in Taiwan, Haspolat et al (2005) in Turkey, Matsuo et al (2006) in Japan, and Capurso et al (2010) in the USA. In addition, Tilgen et al (2002) and Tsai et al (2002) found that the C allele was most frequently observed in febrile seizure patients in German and Taiwanese populations, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…(5) In this regard, a functional polymorphism of cytokine genes is of great interest, since these proteins contribute most to the regulation of immunity, in epilepsy as well. (6)(7)(8) The most frequent causes of differences in gene structure are point mutations, tandem repeats of parts of the gene, and deletions of nucleotides or small gene fragments. The mutant fragments of one or several genes, located very close to each other, can be inherited together (coupling) as the result of selective advantages or, more typically, because of the irregularities of meiotic recombination in this chromosomal region.…”
Section: Introductionmentioning
confidence: 99%
“…The mutant fragments of one or several genes, located very close to each other, can be inherited together (coupling) as the result of selective advantages or, more typically, because of the irregularities of meiotic recombination in this chromosomal region. (5)(6)(7) Multiple animal studies have shown that the components of the immune response can play some role in FS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%